Compliance with Antihypertension Medication In the Community Of Rambutan District South Sumatera - Fitriani, Nyayu; Mayasari, Ni Made Elva; Rosita, Yanti; Indriyani, Indriyani; Handayani, Susi; Erlyn, Putri (Syifa'Medika, 2025)
Adherence to treatment is very important for hypertensive patients to control and prevent complications. This study aims to describe the level of adherence to antihypertensive drugs in hypertensive patients in Sungai Pinang Village, Rambutan District, Banyuasin Regency, South Sumatra, Indonesia. This research is a quantitative research with a descriptive type of research with a cross sectional research design. The sample size was 80 respondents with inclusion criteria aged ?40 years, using antihypertensive medication for at least two months before the study. Data was obtained using interviews using the Indonesian version of the Medication Adherence Report Scale Questionnaire and has been validated. The research results showed that 80 patients with hypertension had a prevalence of adherence to treatment of 8.75%. Most of the patients who adhere to treatment are aged 70-72 years, female, not working, college education level, long suffering from hypertension ?5 years, comorbidities with heart disease, no health insurance, no family support, number of medications ?1 type antihypertensive drugs. In conclusion, the level of compliance with taking antihypertensive medication in the Rambutan District Community of South Sumatra is not good.